Ecobrick Method To Reduce Plastic Waste In Tanjung Mekar Village, Karawang Regency - Ariyani, Dwi; Warastuti, Niken; Arini, Resti Nur (Fakultas Teknik UB, 2021)
According to a survey by Nova Chemicals, Indonesia is the second largest contributor to sea waste after China, which is 1.29 million metric tons / year. At present there are still many people in Indonesia who throw garbage in any place, and can caused flooding in the river. The river is polluted with a lot of waste, one of which is the Citarum River. Citarum River is a river that is very important for residents of West Java. The condition of the Citarum River which is very alarming is polluted by waste and garbage. In the world's leading survey site, the Citarum River occupies the 4th position for the dirtiest river problem. The rubbish that pollutes the Citarum River is more inorganic or unbiodegradable, for example plastic, bottles or beverage cups, plastic food wrapping, and so on. As we know plastic waste is very difficult to decompose, it takes more than 100 years to decompose the plastic decomposed or decompose completely. Plastic waste is one source of environmental pollution in Indonesia. The benefits of using plastic products must be balanced with the calculation of the negative impact produced. The nature of this plastic material makes it difficult to replace it with other materials for various applications, especially in everyday life ranging from food packaging, household appliances, children's toys, electronics to automotive components. Increased use of plastic materials has resulted in increased production of plastic waste from year to year. The destruction of plastic waste by burning will only worsen the health because of the anti-dioxy substance produced. The most appropriate method used in dealing with waste is to use the Ecobrick method. The team of Pancasila University wanted to socialize how to make an ecobrick, and how strong the compressive on the ecobrick material was made. To overcome waste, especially plastic along the Citarum river. This socialization was held in Tanjung Mekar Village, Karawang Barat sub-district, Karawang Regency. The participants coming from the community of environmentalists (Eco Village). Community of eviromentalists hope will provide direction and socialization to their about the ecobrick method to deal with plastic waste that cannot be recycled. From the results of testing carried out at the Pancasila University concrete laboratory using ecobrick materials is plastic bottles filled with pure plastic, filled with sand, and a mixture of plastic and sand compared to red brick and concrete brick sold in the market, from the compressive strength test results it is known that the material ecobrick which contains of sand shows the greatest compressive strength value is 41.2 Mpa, compared to red brick which is 27 Mpa and concrete brick is 38 Mpa ecobrick has a higher compressive strength than other materials.